An auxiliary diagnostic approach based on traditional Chinese medicine constitutions for older patients with frailty - Xuchao Gu; Xiaojun Wang; Yijing Yang; Kangwei Guan; Hung‐Chen Chang; Dehua Liu; Wenhao Wang; Tao Wu; Peiqing He; Jiaofeng Wang; Jie Chen; Zhijun Bao (Clinical and Translational Discovery)
Abstract Introduction As global population ages, frailty has surfaced as a major public health challenge. Given the heterogeneity of frailty in the clinical presentation, it is imperative to develop personalised diagnostic and treatment strategies. The traditional Chinese medicine (TCM) constitution offers notable advantages in discerning individual differences. This study aims to elucidate the association between TCM constitutions and frailty, providing insights into the application of TCM for the frailty management. Methods An observational study was conducted at Huadong hospital from July 2022 to November 2023. A total of 241 older patients were recruited. Each patient underwent assessments for the TCM constitution and frailty status. Comprehensive data collection encompassed medical history, biochemical indicators, bone mineral density (BMD), body composition and physical performance metrics. Plasma samples were also collected to detect levels of inflammatory factors and lymphogenesis‐related factors, including IL‐1β, TNF‐α, VEGF‐C, ANGPTL4 and ACV‐A. Multi‐level statistical analysis was used to establish the relationship of TCM constitutions with frailty. Results Amongst all participants, 54 individuals were classified as non‐frail, 90 individuals as pre‐frail and 97 individuals as frail. Regression analysis indicated that frailty was closely associated with four imbalanced TCM constitutions: Qi deficiency, phlegm dampness, blood stasis and Qi depression. Subsequent analysis demonstrated that Qi deficiency was associated with decreased BMD, phlegm dampness with elevated high‐density lipoprotein levels, Blood stasis with elevated blood glucose levels, and Qi depression with both decreased BMD and elevated low‐density lipoprotein levels. Furthermore, individuals characterised by imbalanced TCM constitutions exhibited inferior handgrip strength, walking pace, lower limb strength and higher levels of inflammatory factors and lymphogenesis‐related factors compared to those with balanced TCM constitution. Conclusion Frailty is independently associated with Qi deficiency, phlegm dampness, blood stasis and Qi depression. Personalised diagnostic approaches based on the TCM constitution may offer valuable insights for directing treatment for older patients with frailty.